Penerapan Perjanjian Kerja Pada UMKM Di Kota Mataram Menurut Undang-Undang No.13 Tahun 2003 Tentang Ketenagakerjaan Dan Undang-Undang No.11 Tahun 2020 Tentang Cipta Kerja - Cahyani Yuniati (Private Law, 2023)
This study aims to determine the arrangements, forms, and types of work agreements based on Indonesian positive law and the application of work agreements to MSMEs in Mataram City. This research is empirical legal research. The approach method used in this research, namely the statutory approach, conceptual approach, and sociological approach. The data used in this study are primary data and secondary data. The results of this study are the regulations stipulated in Law No. 13 of 2003 concerning Manpower and Law No. 11 of 2020 concerning Job Creation. There are two forms of work agreements, namely unwritten and written. As for the type of agreement, namely a work agreement for a certain time and a work agreement for an unspecified time. The application of the work agreement is made orally, meaning that it is not written. The type of work agreement is a work agreement for an indefinite period, observing the status of workers in MSMEs in Mataram City, namely most permanent workers.